WYKŁADNIA EWOLUCYJNA EUROPEJSKIEJ KONWENCJI PRAW CZŁOWIEKA A ZASADA KONSENSUSU. PRÓBA ANALIZY - Soloch, Bartosz (Zeszyty Prawnicze, 2016)
Evolutive interpretation is one of the most important interpretative tools of the European Court of Human Rights (ECHR). It seems quite obvious that it is at least potentially in conflict with one of the most important principles of international law, namely the Principle of Consent (Konsensprinzip). The aim of this article is to shed some light on the question how the Court in Strasbourg tries to reconcile those two principles. It seems that the function of the concept of evolutive interpretation is to set the goal for the interpretation process (i.e. to ensure that the Convention is interpreted accordingly to the requirements of the “present-day conditions”) rather than to govern the technical details of argumentation. The Principle of Consent comes into play in the form of a limitation to the process of evolutive interpretation and may take many forms. The most remarkable of them is the construct of European or international “consensus”, determined mainly with the help of comparative interpretation. It seems that the quality of the comparative method is of essential importance to ensure that evolutive interpretation should not devolve into judicial law-making and, therefore, to secure the legitimation for the rulings of the ECHR.